Effect of Teacher Competence and Student Learning Independence on Achievement Islamic Subjects - Nurhasan; Ahmed, Abdussalam Ali (Sinergi International Journal of Islamic Studies, 2023)
This research is about the influence of teacher competence and student independence on academic achievement of Islamic subjects conducted research at State High School 66 Jakarta. The population in this study were students of class XI Natural Sciences and Social Sciences 64 students were sampled. And this study uses a questionnaire as a tool for collecting data that is related to the problem of influence Teacher competence and student independence for the subject's learning achievement Islamic. That based on the results of the study found in the field about Teacher competence and student learning independence are classified as good but indeed there still must be an increase again, especially for students whose grades are still being carried on average, because there are values ranging between 62-96, it means there is a vulnerable value of 34.